Cumulative dietary exposure to a selected group of pesticides of the triazole group in different European countries according to the EFSA guidance on probabilistic modelling. (May 2015) - Boon, Polly E.; van Donkersgoed, Gerda; Christodoulou, Despo; Crépet, Amélie; D'Addezio, Laura; Desvignes, Virginie; Ericsson, Bengt-Göran; Galimberti, Francesco; Ioannou-Kakouri, Eleni; Jensen, Bodil Hamborg; Rehurkova, Irena; Rety, Josselin; et al.
Highlights: We modelled the cumulative dietary exposure to triazoles in eight European countries. We tested the practicality of the EFSA guidance on probabilistic modelling for cumulative exposure assessments. Optimistic model run can be performed on a routine basis for cumulative assessments. Pessimistic model run is very laborious and may result in very conservative exposure estimates. More experience is needed with the EFSA guidance regarding feasibility of all requirements and need for conservatism. Abstract: The practicality was examined of performing a cumulative dietary exposure assessment according to the requirements of the EFSA guidance on probabilistic modelling. For this the acute and chronic cumulative exposure to triazole pesticides was estimated using national food consumption and monitoring data of eight European countries. Both the acute and chronic cumulative dietary exposures were calculated according to two model runs (optimistic and pessimistic) as recommended in the EFSA guidance. The exposures obtained with these model runs differed substantially for all countries, with the highest exposures obtained with the pessimistic model run. In this model run, animal commodities including cattle milk and different meat types, entered in the exposure calculations at the level of the maximum residue limit (MRL), contributed most to the exposure. We conclude that application of the optimistic model run on a routine basis for cumulative assessments is feasible. The pessimistic model run is laborious and the exposure results could be too far from reality. More experience with this approach is needed to stimulate the discussion of the feasibility of all the requirements, especially the inclusion of MRLs of animal commodities which seem to result in unrealistic conclusions regarding their contribution to the dietary exposure.